A Study on Rural Women Entrepreneurs in Sonitpur District of Assam With Special Reference to Rangapara Development Block - Das, Daisy (AMC Indian Journal of Entrepreneurship, 2022)
Women play a vital role in the development of the society. For the growth of economy, women entrepreneurs are considered as important source. They were treated as the weaker section with less leadership role, but with changing times, now people have started accepting the leading role of women in society. The objective of the research paper is to find out the problems of rural entrepreneurs and motivating factors which influences them to become entrepreneurs. Women entrepreneurs face many problems such as lack of access to formal finance, gender based barriers, cultural and social barriers, limited resources, and access to information etc. Rural women entrepreneurs are an integral part of the economy as they can generate employment and reduce poverty and contribute towards empowerment of women.